The Effect of Emotional Freedom Technique (EFT) Training on Perceived Stress Among Communities at Risk of Leptospirosis Affected by Tidal Flooding - Risna Endah Budiati; Soeharyo Hadisaputro; Mateus Sakundarno Adi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Tidal flooding (banjir rob) in the northern coastal areas of Java causes not only physical damage but also psychological distress, including heightened levels of perceived stress. High perceived stress can weaken psychological resilience in disaster-affected communities. This study aims to examine the effect of EFT training on perceived stress among residents of Sayung District, Demak Regency, who are affected by tidal flooding and at high risk for leptospirosis. One promising intervention to address this issue is the Emotional Freedom Technique (EFT), which combines acupoint tapping with verbal affirmations. This study is a quasi-experimental design with one-group pretest-posttest approach. A total of 82 participants from Bedono Village, Sayung Subdistrict, participated in a single-session EFT training. Perceived stress levels were measured using the Perceived Stress Scale (PSS) before and after the intervention. Data were analyzed using paired sample t-tests. There was a significant decrease in PSS scores after the EFT training, from a mean of 57.09 to 43.20 p 0.000 (p < 0.05). These results indicate that EFT was effective in reducing perceived stress among participants affected by tidal flooding. EFT training significantly reduced perceived stress levels in a community impacted by tidal flooding. This technique can be adopted as a community-based psychosocial intervention to help mitigate the psychological effects of natural disasters.